The Use of Data-Driven Dialogue to teach English - Muhammad Farhan Oniel (Borneo Educational Journal (Borju), 2021)
The term data-driven data-driven dialogue (DDD) has emerged recently as a valuable tool for organizing classroom discussion of any predicted lessons and monitoring students' learning process in the classroo O’Brian, Nocon, and Sands (2010). The background of this study is most of the teachers in Indonesia tend to skip the dialogue process when they teach grammar to their students. These conditions impact the use of inappropriate grammar and decreased student interest in learning grammar, especially in English. Thus, this study aims to describe how data-driven dialogue methods can be applied in English classes for Senior High School students. The research was conducted in one of the Senior High Schools in Yogyakarta. The data collected through the DDD method using the four steps include (1) Predict, (2) Explore, (3) Explain, and (4) Take Action.